ATTITUDES AND MOTIVATION OF DEAF AND HARD OF HEARING STUDENTS FOR STUDYING - Povlakić Hadžiefendić, Meliha (Specijalna edukacija i rehabilitacija, 2019)
Aim of this paper was to determine attitudes and motivation for reading/writing and studying of deaf and hard of hearing (DHH) students and relation of those attitudes and motivation ral proposeibilities H children, DHH pupils, etc. ispitivane spoto success at school. Sample of respondents was comprised of 47 DHH students, both genders, age from 14 to 18 years. Scale for examining interests and an aspiration of students (Suzić, 2003) was conducted. Scale is comprised of eight subscales with 20 statements/indicators of attitudes for activities: studying, sports, music, TV, entertainment, reading/writing, love and dating and social work. Ten statements relate to involvement in aforementioned activities and ten others that concluded possibilities provided by those activities. There were assessments conducted in relation to reading/writing and studying, and a connection between assessments related to general school success has been established. Data was processed by descriptive analysis and Spearman’s correlation coefficient was calculated. The result was moderate connection between assessments of DHH students in relation to reading/writing (ρ=0.61) and studying (ρ=0.55) , and moderate strong connection of the note of probabilities which offer these activities (reading/writing – ρ=0.46 and studying – ρ=0.36) with average school success at significance level at p